Giant Preputial Calculus: The First Reported Case in Malaysia - Tze, Huat Chong; Mohd Zuki Asyraf; Firdaus Hayati; Nornazirah Azizan; Nik Amin Sahid; Ting, Jesse Ron Swire; Andee Dzulkarnaen Zakaria (2018)
Preputial calculus is a relative surgical rarity. It usually happens in elderly men with poor hygiene and uncircumcised penis complicated with phimosis. In the paediatric group, it is usually secondary to phimosis and other urologic and/or neurologic anomalies. Surgical treatment is the mainstay of treatment. Herein, we report a 27-year-old gentleman with preputial stone presented with obstructive uropathy and was successfully treated with surgical intervention. To the best of our knowledge, this is the first reported case of the largest preputial stone in Malaysia.